Experimental food supplementation increases reproductive effort in an antbird in subtropical Brazilian Atlantic Forest fragments - Roper,James J; Lima,André M. X.; Uejima,Angélica M. K. (PeerJ PrePrints, 2014)
Food limitation may interact with nest predation and influence nesting patterns, such as breeding season length and renesting intervals. If so, reproductive effort should change with food availability. Thus, when food is limited, birds should have fewer attempts and shorter seasons than when food is not limiting. Here we experimentally test that increased food availability results in increased reproductive effort in a fragmented landscape in the Variable Antshrike (Thamnophilus caerulescens) in southern Brazil. We followed nesting pairs in five natural fragments (4, 23, 24, 112, 214 ha) in which food was supplemented for half of those pairs, beginning with the first nest. Nest success in the largest (214 ha) fragment was 59%, compared to 5% in the 112 ha fragment and no nest was successful in the smallest (24 ha) fragment. Birds were seen, but evidence of nesting was never found in the two smallest fragments. Pairs with supplemented food were more likely to increase clutch size from two to three eggs, tended to renest sooner (20 d on average) than control pairs. Also, fragment size interacted with breeding and pairs in the largest fragment had greater daily nest survival rates, and so nests tended to last longer, and so these pairs had fewer nesting attempts than those in the 112 ha fragment while more than those in the smallest fragment with nesting (24 ha). Clearly, pairs increased their reproductive effort when food was supplemented in comparison to control pairs and fragment size seems to influence both predation risk and food abundance.
Keywords: breeding season length; renesting intervals; nest predation; forest fragments; Experimental food supplementation; Variable Antshrike